Measurement of Intra-abdominal Pressure in Critically-ill Children - Jyoti Singhal (Journal of Clinical and Diagnostic Research, 2014)
Introduction: It is being increasingly recognized that intraabdominal hypertension is an important cause of organ dysfunction. This pilot study was done to determine the feasibility of measuring intra-abdominal pressures (IAP) in critically-ill children using simple inexpensive equipment available in the PICU. Materials and Methods: This was a prospective study done in the paediatric intensive care unit (PICU) of a tertiary care general hospital. Thirty-two consecutive patients admitted to the PICU, staying for more than 24 h and requiring a urinary catheter were studied. IAP was measured by the intravesical method, using a disposable manometer, twice a day for seven days or till discharge/death, Risk factors associated with IAH were recorded. Results: The majority of the patients had an IAP less than 5 mm Hg. Three patients had grade 1 intra-abdominal hypertension (IAP>12 mm Hg). Conclusion: It is feasible to measure IAP in paediatric patients without the use of sophisticated equipment.